Perception of Tourists towards Local Culture as Demonstrated at Rantau Panjang, Kelantan - RADEN ISMAIL, RADEN MOHD FARHAN HELMY; JUSOH, NUR AINAA SYUHADA; ROHIAT, MOHD AKMAL (Research and Innovation in Technical and Vocational Education and Training, 2021)
The tourism sector is an important sector in generating income and economic growth of the country, especially in a tourist destination. The shape of the terrain in an area is a factor that makes the area a tourist attraction. The culture of the place also plays an important role in making it a unique attraction for tourists. The rate of tourists in Malaysia has increased every year making Malaysia their preferred destination especially at Rantau Panjang, Kelantan. This is because the Rantau Panjang is a place of trade, shopping for visitors coming to Kelantan. In the tourism sector, the safety and culture of visitors is very important to the satisfaction of visitors to Manson, (2008). The culture of the place plays a key role in showing visitors that cultural issues are the custom they use in everyday life. Therefore, visitors to a place no matter where they come from, they need to maintain their culture and customs as visitors. In addition, as a society people also need to accept the culture they bring and only consider their culture and customs as visitors. This research is in the form of quantitative which is done using the questionnaire. It consist of 38 question including demography respondent. The data which is collected was analysed using the software Statiscal Package For Social Sciences (SPSS) version 25.0. Data received were analyzed using descriptive statistic. Results shows the mean score for each of these items to answer the research question. The mean value for questionnaire item B was 3.38 (visitor knowledge of culture at Rantau Panjang , Kelantan), and section C was 3.32 (visitor perception of cultural influence at Rantau Panjang, Kelantan).